The Necessity of Strangers : the Intriguing Truth About Insight, Innovation, and Success. - Gregerman, Alan (Wiley, 2013)
A counterintuitive approach to fostering greater innovation, collaboration, and engagement Most of us assume our success relies on a network of friends and close contacts. But innovative thinking requires a steady stream of fresh ideas and new possibilities, which strangers are more likely to introduce. Our survival instincts naturally cause us to look upon strangers with suspicion and distrust, but in The Necessity of Strangers, Alan Gregerman offers the provocative idea that engaging with strangers is an opportunity, not a threat, and that engaging with the right strangers is.